Clinical and molecular features of thiazide-induced hyponatremia - Nadal, Jodie; Channavajjhala, Sarath K.; Jia, Wenjing; Clayton, Jenny; Hall, Ian P.; Glover, Mark (Springer, 2018)
Hypertension affects more than 30% of the world’s adult population and thiazide (and thiazide-like) diuretics are amongst the most widely used, effective and least costly treatments available, with all-cause mortality benefits equivalent to ACE inhibitors or calcium channel antagonists. A minority of patients develop Thiazide Induced Hyponatremia (TIH) and this is largely unpredictable at the point of thiazide prescription. In some cases TIH can cause debilitating symptoms and require hospital admission. Although TIH affects only a minority of patients exposed to thiazides, the high prevalence of hypertension leads to TIH being the most common cause of drug-induced hyponatremia requiring hospital admission in the UK. This review examines current clinical and scientific understanding of TIH. Consideration is given to demographic associations, limitations of current electrolyte monitoring regimens, clinical presentation, the phenotype evident on routine clinical blood and urine tests as well as more extensive analyses of blood and urine in research settings, recent genetic associations with TIH and thoughts on management of the condition.